Fishes of the Western North Atlantic. order Isospondyli (part), suborder Argentinoidea, suborder Stomiatoidea, suborder Esocoidea, suborder Bathylaconoidea, order Giganturoidei /: order Isospondyli (part), suborder Argentinoidea, suborder Stomiatoidea, suborder Esocoidea, suborder Bathylaconoidea, order Giganturoidei. Soft-rayed bony fishes : Part 4, (1964) - Bigelow, Henry Bryant, 1879-1967; Cohen, Daniel M; Dick, Myvanwy M; Jr, Gibbs, Robert H; Grey, Marion; Morrow, James E (James Edwin), 1918-2002; Schultz, Leonard P (Leonard Peter), 1901-1986; Walters, Vladimir, 1927-
No abstract available